Pengaruh Corporate Governance terhadap Profitabilitas Bank Umum Syariah (BUS) Indonesia Periode 2011-2016 - Ariandhini, Jielend (Universitas Muhammadiyah Malang, 2019)
This study aims to determine the effect of Corporate Governance (CG) as measured by the composition of the board of commissioners, the composition of the board of directors, the composition of the audit committee and the composition of the syariah supervisory board on the profitability of sharia commercial banks as measured by Return On Assets (ROA). The Method of this research is quantitatif by using secondary data with documentation technique. The population used in this study is all sharia commercial banks, based on the financial statements of each bank. The observation period in this research is from 2011 to 2016. The sampling technique is done by purposive sampling method. There are 5 banks, namely Bank Muamalat, Bank Sharia Mandiri, Bank Negara Indonesia Sharia, Bank Rakyat Indonesia Sharia, Bank Central Asia Sharia. Data analysis technique used in this research is panel regression. The results showed that independent variables of board of commissioner and syariah supervisory board have no significant effect on financial performance measured by Return on Asset (ROA). The independent variable of the board of directors has a positive and significant impact on the financial performance measured using Return on Assets (ROA), and the audit committee independent variable has a negative and significant effect on the financial performance measured using Return on Assets (ROA).